Аналіз існуючих способів підвищення якості металопродукції залізничного призначення - Бабаченко, О.І.; Дьоміна, К.Г.; Кононенко, Г.А.; Сафронова, О.А. (Physico-technological Institute of Metals and Alloys, 2020)
The article presents an analysis of existing publications, which highlight the issues of increasing the strength and reliability of the axles of wheelsets. Increasing the strength and service life of axles can only be achieved in a comprehensive manner: by improving the design, by rational choice of material, methods of processing and strengthening them. An important role in this is played by the improvement of the operating conditions of the rolling stock and its maintenance. If earlier there was a tendency to ensure the reliability of the axle operation mainly by increasing the section, now this way has actually exhausted itself and is giving way to methods of increasing the fatigue strength. The opportunities in this area are wide enough. They are the main focus of this article. To solve the problem of improving the quality of axles of railway cars, the following main methods can be distinguished: measures aimed at improving the quality of steel for the production of axles in the process of its smelting (reducing the content of sulfur, phosphorus, hydrogen, etc.); alloying and microalloying of steel for the manufacture of railway axles; improving the processing of the metal of axial blanks in the process of hot deformation; selection and development of optimal modes of heat treatment of axial workpieces. In our opinion, improving the processing of the metal of axle blanks in the process of hot deformation is precisely the way to improve the quality of railway axles, which does not require measures that significantly increase the cost of the existing technology for their manufacture. Since, due to the intense deformation action in ordinary carbon steel, it is possible to improve the quality of its macrostructure, to form a favorable distribution of the hereditary chemical heterogeneity of silicon and manganese in its microstructure, which will ensure the formation of a fine-grained and uniform ferrite-pearlite microstructure. All this will contribute to an increase in the characteristics of plasticity, toughness and strength under cyclic loads of carbon steel for structural purposes, in particular for the manufacture of railway axles.